Antibacterial effect against Streptococcus pneumoniae of bioactive extracts from natural beehives (Apis mellifera) from East Java, Indonesia - Nugraheni, Zjahra Vianita; Anal, Anil Kumar; Santoso, Mardi; Athapol Noomhorm; Muanmai Apintanapong; DirectoratGeneral of Higher Education (DIKTI)Ministry of Education and Culture, Indonesia; AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2013)
Propolis is one of the bee products that produce from beehives besides honeys. Propolis iswell known because it has manybiological activities. The biological activities of propolisare due to its chemical components. Propolis containmanycompounds such as resinouscompounds, balms, beeswax, aromatic essential oil, bee pollen, amino acids, traceelements and at least 38 bioflavonoids.This study mainly uses natural beehives from Lamongan, East Java, Indonesia to getpropolis extract as primary material. It focused on the extraction method using ultrasonicassisted extraction method. It also study propolis composition, antibacterial effect, andminimum inhibitory concentrations (MICs) of Indonesia propolis extract. The amplitudeand time ofextraction have 18 variations according to Design-Expert software, speciallyresponse surface method (RSM). Propolis compositions that characterized are phenolic,flavonoid, protein and carotenoid. Antibacterial activities were examined using pathogens,Escherichia coli,Salmonella enteritidisandStreptococcus pneumoniae, respectively. Forminimum inhibitory concentration, this study only focused on propolis extracts that haveantibacterial activities and useStreptococcus pneumoniaeas pathogen.Propolisextract which produced from different amplitude and time of extraction hasdifferent compositions. These propolis extracts have phenolic, flavonoid and proteincontent. However, carotenoid content of them is almost zero. The sixth propolis extract hasantibacterial effect inS. pneumoniae. MICs test show that 6thpropolis extracts have MICvalue in 1% (v/v) of propolis concentration and have the best MIC value.
A thesis submitted in partial fulfillment of the requirements for thedegree of Master ofScienceinFood Engineering and Bioprocess Technology, School of Environment, Resources and Development
Thesis (M. Sc.) - Asian Institute of Technology, 2013
Keywords: Streptococcus; Anti-infective agents; Extraction